2013
DOI: 10.1002/pssa.201329148
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of CIGS films by hydrazine-free solution method

Abstract: In this paper, copper indium gallium diselenide (CIGS) thin films were deposited by a hydrazine-free solutions method. In the proposed method, acetylacetonate salts and Se powder were simply dissolved in triethylenetetramine under ambient conditions, respectively. These two solutions were mixed in a certain percentage to form the final CIGS precursor solution. CIGS films were obtained by a drop-coating method and subsequently annealed in nitrogen atmosphere. The facile formation of the precursor solution witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…The peak positions of Cu 2p were 931.5 eV (2p 3/2 ) and 951.2 eV (2p 1/2 ) and the split orbit was 19.7 eV. This result confirmed the +1 value of Cu . Similarly, In 3d and Ga 2p peaks demonstrated that the oxidation states of In and Ga were both +3.…”
Section: Resultssupporting
confidence: 60%
“…The peak positions of Cu 2p were 931.5 eV (2p 3/2 ) and 951.2 eV (2p 1/2 ) and the split orbit was 19.7 eV. This result confirmed the +1 value of Cu . Similarly, In 3d and Ga 2p peaks demonstrated that the oxidation states of In and Ga were both +3.…”
Section: Resultssupporting
confidence: 60%
“…7 shows the third system, pure CuInS 2 is chalcopyrite along with wurtzite structures (polytypism) while by substituting Zn 2+ , the chalcopyrite structure is more enhanced and the main peak of the wurtzite structure disappeared even in samples with Zn content (the main structure is chalcopyrite) close to 50%. No segregation was observed even at high Zn concentrations because the radius of the Zn 2+ ion (0.74 Å) 58 is close to that of In 3+ (0.76 Å) and Cu 1+ (0.71 Å). The segregation can be due to Hume-Rothery rules.…”
Section: Resultsmentioning
confidence: 92%
“…However, the best performing CIGS solar cells by this approach is achieved from hydrazine based inks, which prohibits its industrial production for health, environment and safety concerns. Although many other solvents such as anhydrous alcohol, propylene glycol, tetramethylguanidine and triethylenetetramine have been utilized to replace hydrazine, the results are far inferior. Recently, dimethyl sulfoxide (DMSO), which was first used as a solvent by Hillhouse group to make copper zinc tin sulfide (CZTS) precursor solution and demonstrated its success in achieving highly efficient CZTS solar cells, was adopted to chalcopyrite system by the same group and power conversion efficiencies of 13.0% and 14.7% have been achieved for copper indium sulfoselenide (CISSe) and copper indium gallium sulfoselenide (CIGSSe) solar cells .…”
Section: The Device Parameters Of Cisse Solar Cells With the Absorbermentioning
confidence: 99%
“…However, the absorber of the best performing CIGS solar cells are all deposited by vacuum methods such as co‐evaporation and sputtering, which prevent the large scale manufacturing due to complex fabrication conditions, low throughput, and hard control of film homogeneity. Thus, non‐vacuum methods including electrodeposition, nanoparticle ink and molecular precursor solution have been explored to fabricate CIGS absorber thin films with the highest efficiency achieved of 15.4, 17.1, and 17.3%, respectively. Compared to the other two methods, molecular precursor solution approach has many advantages, such as simple solution preparation, high materials utilization rate, adoptable to roll‐to‐roll processing, and precisely control of element composition and large area homogeneity.…”
Section: The Device Parameters Of Cisse Solar Cells With the Absorbermentioning
confidence: 99%